Utilization of the Muara Takus Temple Site as a Source of Historical Learning to Increase Student Motivation and Historical Awareness at the Darussakinah Islamic Boarding School Madrasah Aliyah - Fazira, Eliska; Aman , Aman; Astari, Ayu (ARKA INSTITUTE, 2025)
This study aims to describe the use of the Muara Takus Temple site as a source of historical learning at the Darussakinah Islamic Boarding School Madrasah Aliyah. The research method used is a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation. The research subjects include history teachers, students, and the managers of the Muara Takus Temple site. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the use of the Muara Takus Temple site as a source of historical learning had a positive impact on three areas of learning, namely the cognitive, affective, and psychomotor domains. Factors supporting the implementation of this activity included support from the school, student enthusiasm, and cooperation with site managers. Meanwhile, the inhibiting factors included time constraints, facilities, and teachers' ability to integrate site-based learning into the curriculum. Overall, history learning using the Muara Takus Temple site proved to be effective in increasing learning motivation, fostering appreciation for local history, and strengthening the national identity of students.